PENGARUH LATIHAN PUSH-UP TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA SISWA PUTRA KELAS X SMA NEGERI 1 KUBU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on observations made in the field while doing the shot put sport, it can be seen that the students are not doing well, meaning that their abilities are below the maximum result. Therefore, the researchers went to the cause of the low shot put results. It turned out that the lowest shot was caused by the arm and shoulder muscle strength that was not good. This was the researcher wanted to see the strength of the arm and shoulder muscles in the hope that the strength was good and the result was good. This study aims to see: The effect of push-up training on the muscle strength of the arms and shoulders in class X SMA Negeri 1 Kubu. The population used was class X SMA Negeri 1 Kubu, which 10 people could understand. The sampling technique used total sampling so that the sample numbered 10 students. The instrument in this study was to develop a dynamometer. The collected results were later analyzed using the t-test. Based on the t-test results in a t count of 4.955 with a t table of 1.796, then ha is rejected, at the alpha (α) 0.05 level. It can be concluded that there is an effect of push-up training on the muscle strength of the arms and shoulders in class X SMA Negeri 1 Kubu. Based on the comments above, that push-ups can increase the strength of the arm and shoulder muscles, if given continuous training.Key Words: Push-ups, Arm And Shoulder Muscle Strength